A case series of three cases of Japanese Encephalitis in Aligarh Region: Has the disease taken its tour from east to west UP - Sami, Hiba; Hassaan, Sadia; Ali, Syed Ghazanfar; Raza, Adil; Ahmad, Islam; Mustafa, Zeeshan; Ali, Mohd Kashif; Ur Rab, Zeeba Zaka; Fatima, Nazish; Khan, Haris M (International Journal of Human and Health Sciences (IJHHS), 2023)
Objective: Japanese encephalitis (JE) virus is a flavivirus that is widespread in Asia and is spread via Culex mosquitoes. It is a member of the Flaviviridae family and is one of the most common viral causes of acute encephalitis syndrome (AES) among known etiological viral encephalitis agents, and it has been linked to significant morbidity, death, and disability. We present three cases of acute encephalitis syndrome brought on by the Japanese Encephalitis virus from an area of India that is typically underreported. Material and Methods: Three infants presenting with symptoms of AES were included in the study. Diagnosis of Japanese Encephalitis was made using commercial IgM ELISA kit for JE. HSV I & II was also tested by commercial ELISA kits (Calbiotech). Results: All the three cases presented with abnormal movements and seizures and they all belonged to paediatric age group. They did not have any recent travel history to endemic areas. They were started with empirical and supportive treatment. All the three cases had a unfortunate outcome with mortality on 7th and 9th day of admission. Conclusion: Given the diverse clinical symptoms of the Japanese encephalitis virus, significant effort should be made to pinpoint the specific causal agent that initiates AES. Despite having little effect on management, vector control and vaccination can stop the spread of the disease to healthy contacts and the general public. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S182-S187